(untitled) (Qualitative Research Journal for Social Studies, 2026)
This study examines the role of social media in the political mobilization of youth in Pakistan from 2015 to 2025. Using a qualitative research approach, the study analyzes social media content to understand how platforms such as Facebook, Twitter, Instagram, and TikTok have influenced youth political awareness, engagement, and participation. The findings reveal that social media has played a significant role in mobilizing young people by increasing awareness of national issues, facilitating political dialogue, and encouraging participation in campaigns and online movements. However, the study also identifies challenges, including misinformation, echo chambers, and selective engagement, which in some cases limit critical thinking and informed participation. The study concludes that social media has reshaped youth political participation in Pakistan and emphasizes the need to promote digital literacy, ethical online activism, and inclusive political discussions to ensure constructive and informed engagement among young citizens.